Disrupting board appointments: Australia's governance guidelines and gender capital. Issue 5 (5th February 2021) - Sheridan, Alison; Lord, Linley; Ross-Smith, Anne
Abstract : Purpose: The purpose of this paper is to identify how board recruitment processes have been impacted by the Australian Securities Exchange (ASX) governance changes requiring listed boards to report annually on their gender diversity policy and profile. Design/methodology/approach: Employing a social constructivist approach, the research analyses interviews conducted with matched samples of board directors and stakeholders in 2010 and 2017 about board recruitment in ASX50 companies. Findings: The introduction of ASX guidelines requiring gender reporting disrupted traditional board appointment processes. Women's gender capital gained currency, adding an additional dimension to the high levels of human and social capital seen as desirable for board appointments. The politics of women's presence is bringing about changes to the discourse and practice about who should/can be a director. The authors identify highly strategic ways in which women's gender capital has been used to agitate for more women to be appointed to boards. Research limitations/implications: While sample sizes are small, data within the themes cohered meaningfully across the time periods, making visible how women's presence in the board room has been reframed. Future research could consider what this may mean for board dynamics and how enduring are these changes. Practical implications: This study highlights the forms that human and social capital take in board appointments, which can be instructive for potential directors, and how these intersect with gender capital. The insights from the study are relevant to board recruitment committees seeking to reflect their commitment to a more gender equitable environment. Originality/value: There has been a recalibration of men's and women's gender capital in board appointments, and there is now a currency in femaleness disrupting the historical privilege afforded "maleness".